THE EFFECT OF COMMITMENT AND AMBITION ON BUSINESS PERFORMANCE - Sarja, Sarja (Journal of Islamic enterpreneurship and Management, 2022)
This study aims to examine the commitment, ambition and business performance of Micro Enterprise entrepreneurs in Magelang. The research method was conducted by surveying 100 micro entrepreneurs in Magelang City, through multiple linear regression analysis. Quantitative data were obtained through questionnaires and processed to see the results descriptively and verifiably. The research findings conveyed that there is a relationship between commitment, ambitious entrepreneurship and entrepreneur's business performance. However, the business performance of entrepreneurs from Micro Enterprises in Magelang can be increased more optimally through the commitment of entrepreneurs. This research is useful for the UKM Office in Magelang in particular and entrepreneurs in general, that it is important to pay attention to the commitment of entrepreneurs related to business performance.